Study of possible immune protection with graded doses of Pasteurella multocida type B:2 inoculated orally in mice - Tai, Shen Rong (2016)
Haemorrhagicsepticaemia (HS) is an acute fatal septicaemic disease in cattle and buffaloes caused by Pasteurellamultocida Type B:2 in Malaysia. There is need to develop a vaccine easily administrated compared to those currently used. This study describes the possibility of using graded doses of oral bacterium to induce immunity. A total of 26 mice were divided into treatment groups (Group 1, 2, 3, and 4) each with 5 mice and control (n=6) groups. Treatment groups were inoculated orally with 0.2ml of 103, 105, 107 and 109 colonies forming units (CFU) respectively, while control received 0.2ml of phosphate buffered saline (PBS). Surviving mice were re-challenged with 0.2 ml of 107 CFU orally and observed for another 7 days. Clinical signs, mortality rate and histopathological lesions were examined. All clinical signs were observed to be not significantly (P> 0.05) observed in Group 1 and 2 except (level of alertness and ocular discharges) in Group 3 and 4. Presence of inflammatory cells, haemorrhages and congestions were mild to moderately observed in all treatment groups. However, degeneration and necrosis were observed to be moderate to severe in Group 4. All mice in Group 3 and 4 were euthanized at early stage after second challenged, except Group 1 and 2 with 20% of survival. Bacterial culture from survived mice was significantly lower (P < 0.05) in heart, lung, liver, spleen and kidney. Pasteurellamultocida was confirmed by Gram and Wright’s stains from all positive organ cultures. In conclusion, better survivability was observed in oral bacterium of 103 and 105 CFU with milder clinical signs and histological lesions, while 107 and 109 CFU resulted in detrimental effects on mice. Thus, low but not high dose of oral inoculum was believed to induce immunity and possible to use as oral vaccine.